Role of AzoR, a LysR-type transcriptional regulator, in SmeVWX pump-mediated antibiotic resistance in Stenotrophomonas maltophilia. (21st June 2021) - Lu, Hsu-Feng; Tsai, Yu-Chieh; Li, Li-Hua; Lin, Yi-Tsung; Yang, Tsuey-Ching
Abstract: Background: The SmeVWX efflux pump of Stenotrophomonas maltophilia contributes to menadione (MD) tolerance and resistance to chloramphenicol, quinolones and tetracycline. The components of the SmeVWX efflux pump are encoded by a five-gene operon, smeU1VWU2X . We have previously demonstrated that the smeU1VWU2X operon is intrinsically unexpressed and inducibly expressed by MD via a SoxR- and SmeRv-involved regulatory circuit in S. maltophilia KJ. We also inferred that there should be other regulator(s) involved in MD-mediated smeU1VWU2X expression in addition to SoxR and SmeRv. Objectives: To identify novel regulator(s) involved in the regulation of MD-mediated smeU1VWU2X expression and elucidate the regulatory circuit. Methods: A possible regulator candidate involved in the regulation of MD-mediated smeU1VWU2X expression was identified by a homologue search using the helix-turn-helix domain of SmeRv as a query. Gene expression was assessed using the promoter- xylE transcriptional fusion assay and quantitative RT–PCR. The impact of the regulator on SmeVWX pump-mediated functions was investigated via mutant construction and functional tests (antibiotic susceptibility and MD tolerance). Results: AzoR (Smlt3089), a LysR-type transcriptional regulator, was investigated. In unstressed logarithmically grown cells, AzoR was abundantly expressed and functioned as a repressor, inhibiting the expression of the smeU1VWU2X operon. MD challenge attenuated azoR expression, thus derepressing the expression of the smeU1VWU2X operon in S. maltophilia KJ. AzoR down-regulation-mediated smeU1VWU2X expression was observed in quinolone-resistant and SmeVWX-overexpressing S. maltophilia clinical isolates. Conclusions: AzoR negatively regulates the expression of the smeU1VWU2X operon and SmeVWX pump-mediated antibiotic resistance in S. maltophilia .